From Rupert’s Land to Canada West: Hudson’s Bay Company Families and Representations of Indigeneity in Small-Town Ontario, 1840–1980 - Barclay, Krista (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2015)
By the mid-nineteenth century, Hudson’s Bay Company (HBC) officers were retiring in greater numbers with their Indigenous families outside Rupert’s Land. Much work has been done to uncover the experiences of fur trade families who remained at HBC trading posts or settled in what became the American and Canadian Wests, but there has been little research on those families who left for Britain or colonial Canada. In Canada West, the racial and gendered terrains of their new home communities were complex ones for Indigenous women and their children to navigate. They played roles in both the reification and subversion of racial and gendered imperial hierarchies, and thus came to occupy unexpected and even contradictory positions in family and local historical narratives.